1973
DOI: 10.1042/bj1320821
|View full text |Cite
|
Sign up to set email alerts
|

The plasma transport and metabolism of retinoic acid in the rat

Abstract: The transport of retinoic acid in plasma was examined in vitamin A-deficient rats maintained on small doses of radioactively labelled retinoic acid. After ultracentrifugation of serum adjusted to density 1.21, most of the radioactivity (83%) was associated with the proteins of density greater than 1.21, and not with the serum lipoproteins. Gel filtration of the labelled serum on Sephadex G-200 showed that the radioactive label was associated with protein in the molecular-weight range of serum albumin. On polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(57 citation statements)
references
References 22 publications
0
55
0
2
Order By: Relevance
“…Previous work demonstrated that RA is transported to a variety of tissues in VAD rats given small doses of RA (25). The highest levels of RA were detected in the liver, kidney, and intestine, whereas the lowest levels were detected in the testis and fat pads.…”
Section: Discussionmentioning
confidence: 92%
“…Previous work demonstrated that RA is transported to a variety of tissues in VAD rats given small doses of RA (25). The highest levels of RA were detected in the liver, kidney, and intestine, whereas the lowest levels were detected in the testis and fat pads.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies in the rat showed that vitamin A deficiency alone inhibits the release of RBP from the liver so that the plasma concentration declines to between 25 and 30 % of the normal level while the pool of RBP in the liver increases fourfold (Muto et al 1972; Smith, Muto et al 1973). In the protein and vitamin A doubly-deficient rat the pool of accumulated RBP in the liver is smaller than that for the solely vitamin A-deficient animal, as indicated by the lower peak value of plasma retinol-binding holoprotein (holoRBP) reached after its release from the liverwithin 3-5 h after the xdministration of retinol.…”
Section: )mentioning
confidence: 99%
“…Although hepatic retinyl palmitate did not change in response to protein malnourishment, protein-deficient animals exhibited a large decrease (21.8 nmol/ g liver) in metabolically 'active' retinol. This change cannot arise solely from a reduction of retinol binding protein concentration in the liver tissue as Smith and coworkers estimated that the retinol binding protein concentration in the rat liver is about 120 ÎĽg/g liver [22]. Assuming that these are all holoproteins, the concentration of retinol attributable to retinol binding protein is only 5.7 nmol of retinol/ g liver.…”
Section: Discussionmentioning
confidence: 99%